Bifida spine in a mongrel dog - Case report. - Lempek, Marthin Raboch; Bordelo, João; Veado, Julio Cambraia; Dias, Maria Isabel Ribeiro; Dias, Maria Isabel Ribeiro (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Lempek M.R., Bordelo J., Veado J.C. & Dias M.I.R. [Bifida spine in a mongrel dog - Case report.] Espinha bífida em um cão sem raça definida - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(3):211-213, 2016. Departamento de Clínica e Cirurgia Veterinária, Escola da Veterinária, Universidade Federal de Minas Gerais, Av. Antônio Carlos, 6627, Campus Pampulha, Belo Horizonte, MG 31270-901, Brasil. E-mail: marthinrl@hotmail.com Spina bifida is a congenital bone malformation with incomplete closure of the dorsal vertebral arches, which may occur in association with protrusion of the meninges, spinal cord and meninges due to vertebral defect. Possible triggering phenomena refers to cell hyperplasia tube affecting the dorsal neural tube fusion and vertebral arches, while limiting the vascular blood flow to a defect in the dorsal region of the spine. This disease is described in pets, such as dogs and cats, similarly to the livestock animal disorders such as cattle. Regarding pets, the brachycephalic dogs are most affected especially Bulldogue English, however in mongrel dogs is seldom reported in the literature. The aim of this report was to describe the occurrence of a case of spina bifida on a mongrel dog. In this case, the spina bifida case was diagnosed by radiological examination. It was observed that in addition to spina bifida in the lumbosacral vertebrae and myelomeningocele, there was another genetic defect, such as incomplete closure of some sacral vertebral bodies. Concluding that all puppy animal showing urinary incontinence and fecal incontinence should should be sujected to a complete evaluation for the detection of possible congenital bone malformations, such as spina bifida, independent of breed or species.